Faktor yang Berkaitan dengan Menyusui Eksklusif Ibu Bekerja di Kota Palangka Raya - Yuyun Christyanni (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2019)
The coverage of exclusive breastfeeding in Indonesia is still relatively low, three provinces that have not yet reached the target are Gorontalo, Riau and Central Kalimantan. The coverage of exclusive breastfeeding in Central Kalimantan Province is 27.6%. While in the City of Palangka Raya the coverage of exclusive breastfeeding in 2016 only reached 14.99%, which was the lowest exclusive breastfeeding coverage rate since 2010. The phenomenon of working women in the city of Palangka Raya is increasing today, but exclusive breastfeeding by working women who have children of infant age is of course expected to continue as well as possible. The purpose of this study was to identify factors that influence exclusive breastfeeding by working mothers in the Menteng City Palangka Raya Health Center area. The method used is descriptive analytic with cross-sectional approach. Samples were selected by purposive sampling as many as 60 working mothers who had babies aged 6-12 months. The results of the study revealed 40 exclusive breastfeeding mothers and 20 mothers who were not exclusively breastfeeding. Chi-square analysis showed that there was a significant relationship between the health of mothers with exclusive breastfeeding (p value <0.05) and there was no significant relationship between infant health, education level, level of knowledge, cultural factors, maternal working conditions, family support, health care support and promotion of formula milk with exclusive breastfeeding (p value> 0.05). Providing health information about breast care, prevention of ASI dams and oxytocin massage in breastfeeding mothers need to be improved so that the mother's physical condition is maintained properly so that the breastfeeding process runs smoothly. In addition, it is also necessary to consider the psychological condition of the mother, especially in working mothers, by providing a comfortable working environment for breastfeeding mothers.